2006
DOI: 10.1038/sj.bjc.6602934
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent infiltration by CD8+ T cells and CD4+ T cells is a favourable prognostic factor in non-small-cell lung carcinoma

Abstract: The purpose of this study was to clarify the relationship between the number of tumour-infiltrating T lymphocytes and the clinicopathological features and clinical outcome in patients with non-small-cell lung cancer (NSCLC). Tissue specimens from 109 patients who underwent surgical resection for NSCLC were immunohistochemically analysed for CD4 and CD8 expression. Patients were classified into two groups according to whether their tumours exhibited a 'high' or 'low' level of CD8 þ or CD4 þ lymphocyte infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
270
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(297 citation statements)
references
References 33 publications
20
270
4
3
Order By: Relevance
“…In stage IV NSCLC patients with chemotherapy, CD8 + T cells in cancer nest link to a favorable outcome, 19 but some other studies suggested that they could not demonstrate an influence on survival of lung adenocarcinoma patients. 2022 A recent study using in silico analysis of tumor immunity also underpinned this conclusion, when taking patient age and stage into consideration. 23 …”
Section: Discussionmentioning
confidence: 91%
“…In stage IV NSCLC patients with chemotherapy, CD8 + T cells in cancer nest link to a favorable outcome, 19 but some other studies suggested that they could not demonstrate an influence on survival of lung adenocarcinoma patients. 2022 A recent study using in silico analysis of tumor immunity also underpinned this conclusion, when taking patient age and stage into consideration. 23 …”
Section: Discussionmentioning
confidence: 91%
“…The reduced number of CTLs at this site may facilitate the dissemination of neoplastic cells and the development of metastases. According to Hiraoka et al (2006), CD4+ helper T cells also play an important role in the antitumor defense by releasing cytokines such as IL-2 and IFN-γ, which are essential for the differentiation of CTLs into effectors cells and exert antitumor and antiangiogenic activity. In the present study, anti-CD4 antibody expression was detected in most specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in tumor blood flow and oxygenation associated with hyperthermia [44], improved vascular adhesion may theoretically enhance T lymphocyte infiltration into tumor sites, as has been reported for natural killer lymphocytes [22]. T lymphocyte infiltration is critical to antitumor responses and improved patient survival [45][46][47]. Although local hyperthermia in combination with other local intratumoral therapies such as vaccination, ablation, or radiation have potential efficacy by improving lymphocyte infiltration [48][49][50], the role of WBH alone as a modifier of the tumor microenvironment has not been established in the context of improving vascular adhesion.…”
Section: Clinical Implications Of Thermal Therapy Dynamicsmentioning
confidence: 97%